O efeito de humor na construção de piadas com teor racista – um caminho para a compreensão? - Santos, Diana Silva (2019)
It is known that working on language teaching is a great challenge for teachers in this area, as there are, among other issues, records of failure regarding the development of reading and writing practices, skills so fundamental to language proficiency presented by different levels of learning. The results of exams such as PISA and SAEB confirm this scenario. In addition to an empirical test carried out in a 7th-grade elementary school classroom in the city of Feira Nova / SE, it was found that the students found it difficult to identify the humor effect presented to them. Given the importance of this ability to the social universe, this study sought to verify, from the application of the Pedagogical Notebook entitled "Charts of humor", "The effect of humor in the construction of racist jokes - a path to textual understanding?" , as the identification of the elements responsible for the construction of the humor effect, in the joke genre, would function as an exercise for textual comprehension. To this end, we adopted the perspective that language is a means of socio-cultural interaction, and the teaching-learning process should be done from the text, with emphasis on textual comprehension and production. The work of: i) Muniz (2004) and Possenti (1998), with regard to the conception of the joke as a textual genre; ii) studies by Possenti (1998), Raskin (1987) and Travaglia (1990) on humor processing from a linguistic point of view; iii) the procedural perspective of writing highlighted in Passareli (2012); and iv) the teaching practice focused on textual understanding presented by Mascus (2008). Methodologically, the Notebook was structured in five stages: i) reflection on ethnoracial prejudice, as well as on the importance of the production process, reception and circulation of humor texts - the joke; ii) presentation of the genre joke, along with the identification of the linguistic elements that define it as belonging to the narrative sequence; iii) identification of strategies used to construct the humor effect in the joke genre; iv) jokes, focusing on the production of explanatory notes and text comprehension; and v) exhibition of a playful activity, constructed with the texts produced by the students in the previous stage. The analysis of this application showed positive results, in that it managed to involve students in interactive practices of reading and writing development, skills essential to language proficiency, based on a reflection on sociohistorical and cultural aspects related to a genre little worked in the classroom. By extension, it could be seen that the identification of the humor effect served as a propelling tool for understanding, seen here as a form of textual production. In this sense, critical reflection and the development of specific Portuguese language teaching skills, linked to social value, have contributed to fostering the students' citizenship, since they have focused not only on a topic, but on a gender, but in seeking to understand the mechanisms that a language user can validate to produce meaning (s) in their respective texts.